Exercise stress testing before and after successful multivessel percutaneous transluminal coronary angioplasty - Chalela,W.A. (2006)
Controversy exists regarding the diagnostic accuracy, optimal technique, and timing of exercise testing after percutaneous coronary intervention. The objectives of the present study were to analyze variables and the power of exercise testing to predict restenosis or a new lesion, 6 months after the procedure. Eight-four coronary multi-artery diseased patients with preserved ventricular function were studied (66 males, mean age of all patients: 59 ± 10 years). All underwent coronary angiography and exercise testing with the Bruce protocol, before and 6 months after percutaneous coronary intervention. The following parameters were measured: heart rate, blood pressure, rate-pressure product (heart rate x systolic blood pressure), presence of angina, maximal ST-segment depression, and exercise duration. On average, 2.33 lesions/patient were treated and restenosis or progression of disease occurred in 46 (55%) patients. Significant increases in systolic blood pressure (P = 0.022), rate-pressure product (P = 0.045) and exercise duration (P = 0.003) were detected after the procedure. Twenty-seven (32%) patients presented angina during the exercise test before the procedure and 16 (19%) after the procedure. The exercise test for the detection of restenosis or new lesion presented 61% sensitivity, 63% specificity, 62% accuracy, and 67 and 57% positive and negative predictive values, respectively. In patients without restenosis, the exercise duration after percutaneous coronary intervention was significantly longer (460 ± 154 vs 381 ± 145 s, P = 0.008). Only the exercise duration permitted us to identify patients with and without restenosis or a new lesion.